The Nexus Between Foreign Direct Investment and Economic Growth in Malaysia - Chong Siew Huay; Najaa Aqilah Arabi; Chuah Soo Cheng (Information Management and Business Review, 2024)
In recent decades, Foreign Direct Investment (FDI) has become a significant factor in promoting economic growth. Recent years have witnessed significant discourse regarding the relationship between foreign direct investment and economic growth. This research employed the Autoregressive Distributed Lag (ARDL) methodology to analyze the long-run and short-run relationships between foreign direct investment and economic growth in Malaysia over the period from 1990 to 2022. The findings indicate that foreign direct investment has a positive impact on economic growth in both the short and long term. This aligns with the fundamental principles of endogenous growth theory, which posits that foreign direct investment enhances the transfer of skills that enrich the knowledge base of the host country in both the short and long term. The study provides policymakers with insights regarding the relationship between economic growth and foreign direct investment (FDI).